MUSIC AND COMMUNICATION. A FIELD OF DISPUTE - Madrigal, Néstor Andrés Caetano (Facultad de Periodismo y Comunicación Social, 2018)
The author raises the need to construct a view from the communication around the aesthetic political analysis of the music. After a short tour of the field of Argentine popular music, parts of a tour of different academic and journalistic views on the subject and then develop the concept of «field», developed by Pierre Bourdieu as the axis of the proposed work.